Power Mask Of Hmps Pips Senior Students In Ldkm Pips New Studentsfaculty Of Social Sciences And Law, Makassar State University - Dewi Reca Litha; Andi Agustang; Andi Dody May Putra Agustang (Jurnal Indonesia Sosial Teknologi, 2023)
This study aims to analyze the construction work of senior students in the LDKM of new PIPS students and analyze the factors of the construction of senior students in the LDKM of new students of PIPS. To achieve the objectives of the study, a Phenomenology-Hermeneutics research approach was used by Heidegger. The data were analyzed using interpretation analysis methods and Nvivo data analysis program version 12. The results showed (1) The construction work of HMPS PIPS senior students in LDKM (Basic Leadership Training) activities began with a narrative of skills, skills, leadership, agents of change, the title of God and students who have. The presence of this ideal fantasy (object a) makes them participate in LDKM (Basic Leadership Training) activities in which they are dominated through the path of requiring understanding of the materials in LDKM (Basic Leadership Training) which are covered with symbolic violence that works through euphemizations leading to psychological and physical violence as a closure. (2) The working factor of HMPS PIPS senior students in LDKM (Basic Leadership Training) activities is because it maintains the existence of the HMPS PIPS internal institution with the aim of competing for the position as President of BEM (Student Executive Board) from the Faculty to University levels, where HMPS PIPS senior students, especially alumni, get pride and recognition as senior figures who create new PIPS student cadres (maba) who can occupy as President of BEM (Student Executive Board). Through their cadre positions, HMPS PIPS senior students gain a platform to channel their knowledge in gaining an image as a senior figure and political interests of the mass base as well as being able to control and control them because they consider them to be senior figures who have experience and knowledge capital in the institutional system that must be respected and feared.